2021
DOI: 10.1155/2021/8028427
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Pinosylvin Extract Retinari™ Sustains Electrophysiological Function, Prevents Thinning of Retina, and Enhances Cellular Response to Oxidative Stress in NFE2L2 Knockout Mice

Abstract: Chronic oxidative stress eventually leads to protein aggregation in combination with impaired autophagy, which has been observed in age-related macular degeneration. We have previously shown an effective age-related macular degeneration disease model in mice with nuclear factor-erythroid 2-related factor-2 (NFE2L2) knockout. We have also shown pinosylvin, a polyphenol abundant in bark waste, to increase human retinal pigment epithelium cell viability in vitro. In this work, the effects of commercial natural pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…For example, NFE2L2 controls catalase and ALDH3, whereas FOXO (forkhead box transcription factor of the class O) and NF-κB (nuclear factor kappa B) regulate the expression of SOD enzymes [ 27 ]. Recently, pinosylvin, an analog of resveratrol, was found to activate both catalase and SOD1 in a mouse model of age-related macular degeneration possibly due to the dual effect of pinosylvin and its metabolite resveratrol on NFE2L2 and SOD regulating transcription factors, respectively [ 68 ]. Pinosylvin or a combination of molecules capable of activating the antioxidant defense system in a wide spectrum would possibly offer a higher impact on cellular wellbeing than molecules targeted to a single transcription factor.…”
Section: Discussionmentioning
confidence: 99%
“…For example, NFE2L2 controls catalase and ALDH3, whereas FOXO (forkhead box transcription factor of the class O) and NF-κB (nuclear factor kappa B) regulate the expression of SOD enzymes [ 27 ]. Recently, pinosylvin, an analog of resveratrol, was found to activate both catalase and SOD1 in a mouse model of age-related macular degeneration possibly due to the dual effect of pinosylvin and its metabolite resveratrol on NFE2L2 and SOD regulating transcription factors, respectively [ 68 ]. Pinosylvin or a combination of molecules capable of activating the antioxidant defense system in a wide spectrum would possibly offer a higher impact on cellular wellbeing than molecules targeted to a single transcription factor.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that chronic oxidative stress eventually leads to protein aggregation in combination with impaired autophagy, as seen in AMD, Tamminen et al [85] investigated the effects of commercial natural pinosylvin extract, Retinari™, on electroretinogram, optical coherence tomogram, autophagic activity, antioxidant capacity, and inflammation markers in their study. For 10 weeks before the experiments, wild-type and NFE2L2 knockout mice were given either ordinary or Retinari™ chow.…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%